Product Subassembly Standardization in Engineer-To-Order Product Delivery Strategy: The Benefits and Drawbacks: Case ABB - Rossi, Timo (My University, 2010)
Everything does not have to be fully customized and flexible even when company is operating based on engineer-to-order product delivery strategy. Company can achieve significant benefits by standardizing and modularizing some subassemblies and -systems of the complex final products. The purpose of this Masters’ Thesis was to investigate the benefits and drawbacks that are caused because of product subassembly standardization when company is operating based on engineer-to-order product delivery strategy. This paper considers the topic from real-life case example point of view. The thesis was made for company ABB. In this research paper the theoretical background and the context of the topic are presented and discussed based on scientific articles and literature. The main theories that are applied are the structures of supply chains, product standardization & modularization and postponement strategy. The empirical part of the paper firstly presents the background of the standardization work. After that the standardization project itself is described. This part reflects the practical real-life case example application to the theoretical background analysis. Finally, as a main result of this thesis, the analysis and summary of the benefits and drawbacks of the subassembly standardization work at ABB are presented and discussed. Cost analysis is in significant role in the final part of the paper.
Keywords: standardization; modularization; postponement strategy; product delivery strategies; fi=Tuotantotalous|en=Industrial Management|